(untitled) (Damascus University Journal of agriculture sciences, 2022)
The research was carried out on 156 Ross 308 chicks hatched from 4 groups, Control (37.8°C during incubation and 37.5°C during hatching), and 3 groups of thermal manipulation (41°C/ 3h/ day): Group 2 (on d 14 and 15 of incubation), Group3 (on d 14-16 of incubation), and Group 4 (on d 14-16 and 18-19 of incubation). Research was applied in the end of summer and ambient temperature was registered 3 times/ day. Thermal manipulation positively and significantly affected body weight of the 3 groups from day 1 to day 28 after hatching, during which ambient temperature ranged between 34.5-36°C. On day 1, body weight of group 2 and 4 chicks exceeded that of control by 1.93g and 3.29g, respectively. Birds of thermal manipulation groups achieved significantly higher body weight average than that of the control as following (226.8g, 513.77g, 960.32g,1617.14g) for group2, (224.45g, 516.42g, 986.78g,1650.09g) for group3, and (220.37g, 498.00g, 972.33g,1611.56g) for group4 compared to (191.31g, 411.04g, 858.01g,1467.67g) for control in week1, 2, 3, and 4, respectively. Thermal manipulation significantly decreased feed intake average of (1-6) weeks in group2 (88.82g) and 4 (92.71g) compared to control (108.22g). There was no significant effect of thermal manipulation on daily body weight gain of (1-6) weeks compared to control and values were 57.45g, 57.84g, 57.36g, 58.47g for control, group2, 3 and 4, respectively. Thermal manipulation significantly decreased feed conversion ratio (FCR) of (1-6) weeks, and FCR of group 2 (1.53) and 4 (1.59) were less (better) compared to FCR of control (1.88), whereas there was no effect of thermal manipulation on mortality during the period of 1-42 days after hatching.